The dark and potentially bright sides of work-avoidance goal orientation - Thea Ebert; Rieke Först; Tanja Bipp (Frontiers in Organizational Psychology)
Goal orientations represent a key approach for explaining employee motivation and performance. While a trichotomous framework (learning, performance-approach, and performance-avoidance goal orientations) dominates the work literature, goals regarding the work process, for example, minimal work expenditure, fall outside the scope. This is reflected in a lack of theoretical differentiation and validated instruments for assessing work avoidance goals in the work context. However, a minimization of effort among employees can pose a risk to the goals of many organizations. Therefore, we extend goal orientation theory at work by building on educational research and introducing the dimension of work avoidance goal orientation to the work context. In three studies of German employees (N1 = 115, N2 = 224, N3 = 121), including cross-sectional and cross-lagged data, we developed a reliable and construct-valid scale to assess work-avoidance goal orientation at the workplace. Furthermore, we reveal contradicting implications from an organizational (prediction of absenteeism/withdrawal behaviors) and an individual perspective (protecting influences in the form of reduced demands), thereby offering starting points for future research and organizational practices that seek to better differentiate in the lower performance and motivation ranges of employees.